Characterization of The essential oil of Eucalyptus Leaves (Melaleuca leucadendra) from Pontianak City and Its Activity Against Streptococcus mutans - Wibowo, Muhamad Agus; Rendi, R.; Warsida, W.; Ardiningsih, Puji; Jayuska, Afghani (Jurnal ILMU DASAR, 2023)
Eucalyptus plants can grow in the city of Pontianak, which is an area with peat soil, although in fact, this plant can grow well in swamps, sandy areas, and mangroves. The difference in the location where eucalyptus grows, causes a difference in the composition of the compounds contained in it, especially 1.8 cineol which is a potential compound to prevent dental caries. This study aims to isolate and characterize the essential oil of eucalyptus leaves from the city of Pontianak and determine its activity in inhibiting the S. mutans bacteria. This research was carried out in two stages: isolating, characterizing, and determining the chemical content of eucalyptus leaf essential oil from Pontianak using Gas Chromatography-Mass Spectroscopy (GC-MS). The second stage was to test the antibacterial activity in inhibiting the growth of S. mutans bacteria using the well diffusion method. The results of the isolation of essential oils obtained a yield of 0.58% (w/w) with a specific gravity characteristic of 0.9288 g/mL, a clear greenish-yellow color, and a characteristic smell of eucalyptus oil, and is soluble in 70% ethanol. GC-MS analysis showed that there were 29 compounds, with the main compound being 1.8 cineol as much as 55.71%. The results of the antibacterial activity test against S. mutans showed that the samples at all test doses were antibacteria with inhibition values of 9.03 mm (1.393 mg/well), 6.76 mm (0.697 mg/well), 6.53 mm (0.348 mg/well), and 5.39 mm (0.174 mg/well). The follow-up test showed that at all doses of the essential oil, it was bacteriostatic against S. mutans bacteria. From the study results, it can be concluded that Pontianak eucalyptus oil meets the standards of SNI 06-3954-2006 with 1.8 cineol as the main compound and has antibacteria properties against S. mutans.